Research and training partnership to assist policy and capacity building in improving food safety in Vietnam - Hung Nguyen-Viet; Grace, Delia; Phuc Pham Duc; Sinh Dang-Xuan; Toan Luu-Quoc; Unger, Fred; Vlieger, S. de; Ngoc Pham Thi; Nhiem Duong-Van; Long Nguyen-Hung; Luan Tran-Dinh; Tran Thi Tuyet Hanh (Elsevier, 2018)
This paper evaluated the implementation of an initiative for promoting risk-based approaches to improve food safety management in Vietnam. A Taskforce of Risk Assessment for Food Safety (Taskforce) was formed and consisted of researchers working on risk assessment and food safety, and representatives of the related ministries of Health and of Agriculture. We used the OECD Development Assistance Committee Evaluation Criteria as a framework for assessing the impact of the Taskforce with five evaluation areas – relevance, effectiveness, efficiency, impact and sustainability. They analysed current food safety policies, identified key constraints and opportunities, and conducted action research and capacity building to address these challenges in food safety. Stakeholder workshops helped determine priority food safety issues and activities. A series of hands-on training based on real-world case studies were organized and risk assessment curricula were developed and taught at universities to promote sustainability. Practical guidelines, text books, a special edition and policy briefs were published. The Taskforce provided technical support to a national food safety assessment commissioned by the World Bank and evidence for development partners. The Taskforce was institutionalized by a national university to have a formal role in implementing its activities. In conclusion, the Taskforce has brought experts in Vietnam to work together on prioritized topics of food safety risk assessment, assisted and informed ministries in implementing risk-based approaches for food safety management. It can be recommended as a way of institutionalising risk-based methods in countries new to the approach.